Las músicas amerindias del Chaco argentino entre la hibridación y la exotización - Silvia Citro; Soledad Torres Agüero (Journal de la Société des Américanistes)
Starting from the musical piece Qom Llalec (« Son of the Qom ») of Toba or Qom musician Romualdo Diarte (Formosa, Argentina), which became the first CD of indigenous music produced by the Culture Department of this province, we discuss the impact of recent cultural policies in the music of these peoples. The hypothesis is that this musical piece evidences the political strategy of the provincial government for legitimating the imaginary of a « multicultural identity » that revalorizes the Chaco Indians, responding in this way to demands of multiculturalism and patrimonialization of national and global policies. Nevertheless, the processes of hybridization, exoticization and invisibilization of the indigenous also reveal the tensions and inequalities that persist in the relationships among government, creoles and indigenous people, as well as the tactics of the latter to address them.